2015
DOI: 10.1039/c5gc00025d
|View full text |Cite
|
Sign up to set email alerts
|

A cellulose sponge with robust superhydrophilicity and under-water superoleophobicity for highly effective oil/water separation

Abstract: A cellulose sponge with properties of superhydrophilicity and under-water superoleophobicity gives 99.94% separation efficiency in oil–water emulsion separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
143
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(144 citation statements)
references
References 39 publications
1
143
0
Order By: Relevance
“…Thus, the further enforcement of membrane was needless in the fabrication process, differing from other reported cellulose porous materials. [23] In addition, the oil contact angles for isooctane were 155, 154, and 154°, in NaCl (1M), HCl (1M), and NaOH (1M), respectively (Fig. S13), revealing that the TCNC membranes could tolerate acidic, salty, and alkaline environments.…”
Section: Durability and Stability Of Tcnc Membranesmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, the further enforcement of membrane was needless in the fabrication process, differing from other reported cellulose porous materials. [23] In addition, the oil contact angles for isooctane were 155, 154, and 154°, in NaCl (1M), HCl (1M), and NaOH (1M), respectively (Fig. S13), revealing that the TCNC membranes could tolerate acidic, salty, and alkaline environments.…”
Section: Durability and Stability Of Tcnc Membranesmentioning
confidence: 94%
“…These results revealed that hydroxyl groups on the surface of TCNCs made the membrane oleophobic, and the formation of cholesteric architecture in the membrane produced superoleophobicity. [23,24] On the other hand, the contact angle of water on the membrane under oil decreased from 132.7° to 31.6° with the increase of thickness of TCNC membranes, indicating the variation of wettability of membranes (from hydrophobicity to hydrophilicity), which will give them the ability to separate water-in-oil emulsion. We should emphasized that the wettability of TCNCs membrane was independent of membrane thickness after the nylon membrane was fully covered, and cholesteric architecture completely formed (dosage ≥ 0.73 g m -2 ).…”
Section: Wettability Of Tcnc Membranesmentioning
confidence: 95%
See 1 more Smart Citation
“…7 However, the applied templates at one size scale usually produce porous materials containing single size scale pores, thus the combination of multiple templates strategies is necessary for hierarchical porous materials. 10,11 Herein, we report multifunctional polymer monoliths with hierarchical porosity without any template and further treatment which is green, simple and environment benign. 9 The fabrication of templates of special nanostructures and removal of hard templates lead to tedious procedure and inevitable limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first material which can separate oil/water from both layered and emulsion oil/water mixtures. Wang et al [71] reported a cellulose sponge with robust superhydrophilicity and under-water superoleophobicity for highly effective oil/ water separation. Smart surfaces are able to switch between superoleophilicity to superoleophobicity in presence of water on any other stimuli like pH or temperature.…”
Section: Absorption Based Separationmentioning
confidence: 99%